Profil Kemampuan Pemecahan Masalah Siswa SMA: Konteks Penggunaan Media Pembelajaran Fisika Berbasis PBL pada Pemanasan Global - Anafiarsih Meliyanti; Insih Wilujeng; Heru Kuswanto (Postgraduate, University of Mataram, 2024)
Problem-solving ability is important for students to have. This is useful for students as an effort to be able to address every problem in real life critically. This study aims to analyze students' problem-solving abilities after using physics learning media based on problem-based learning (PBL). This problem-solving ability is carried out on global warming material on the greenhouse effect. The subjects of this study were 35 students of class XI MIPA 4 at SMA N 1 Depok, Yogyakarta. The method used in this research is the descriptive analysis method. Data collection was carried out by observation and written tests. Based on the results of the analysis of students' problem-solving abilities, an average score of 75.37 was obtained in the very high category. Analysis of each indicator, including identify problems obtaining an average score of 72.22 (high category), diagnose problems obtaining an average score of 74.07 (high category), formulate strategic alternatives obtaining an average score of 79.63 (very high category). high), determine and choice strategy obtain an average score of 77.78 (very high category), and indicators evaluate the success of the strategy obtain an average score of 73.15 (high category).